Analisis Potensi Sumberdaya Air Daerah Aliran Sungai Singkil Menggunakan Model Tangki - Mustafril Mustafril (Department of Agricultural Engineering, Syiah Kuala University, 2014)
Abstrak. Kebutuhan air terus meningkat seiring pertumbuhan penduduk, sedangkan air yang tersedia tidak selalu sejalan antara kebutuhannya menurut volume, tempat, waktu dan kualitasnya. Model-model hidrologi berdasarkan Tank Model telah dikembangkan dalam penelitian di Indonesia dan di dunia untuk memprediksi potensi sumberdaya air dalam suatu DAS. Optimasi parameter Tank Model dapat menggunakan Artificial Neural Network (ANN) yang mempunyai kemampuan untuk belajar dari data dan tidak membutuhkan waktu yang lama untuk mencapai model optimal. Tujuan analisis ini untuk menentukan seberapa besar potensi sumberdaya air di DAS Singkil berdasarkan optimasi parameter Tank Model. Hasil optimasi keseimbangan air parameter Tank Model DAS Singkil meliputi: karakteristik hidrologi DAS Singkil meliputi debit minimum 3,60 mm/hari, debit maksimum 17,80 mm/hari, dan rasio debit maksimum/minimum 4,94. Indikator kesalahan Tank Model DAS Singkil meliputi: R (Coefficient of Correlation) sebesar 0,6471, MAE (Mean Absolute Error) dan RMSE (Root Square Mean Error) masing-masing 2,18 dan 2,73. Total inflow 3.189,48 mm/tahun dan total outflow 3.155,64 mm/tahun, yang terdiri dari: surface flow 11,75 mm/tahun, subsurface flow 669,84 mm/tahun, intermediate flow 62,05 mm/tahun, subbase flow 0,74 mm/tahun, dan base flow 2.411,26 mm/tahun. Berdasarkan total baseflow volume ketersediaan air total yang mengalir di Sungai Singkil mencapai 12.164 x 106 m3/tahun. Potensi sumberdaya air DAS Singkil untuk keperluan pertanian mencapai 3.438,4 x 106 m3/tahun Analysis of Potential Water Resources at Singkil Watershed using Tank Model Abstract. Water demand continues to increase as the population growth, while the availability of water is not always consistent with the needs in terms of volume, place, time and its quality. Tank based hydrological models have been developed in many researches in Indonesia and in the world to predict the potential of water resources in a watershed. The optimalization of tank model parameter could be performed by using Artificial Neural Network (ANN), which has the capability to review the data and does not need much time to reach its optimized model. The purpose of this analysis is to determine the extent of a water resource potential in the Singkil Watershed based on the optimalization of Tank model parameter. Results of the optimalization of water balance of tank model parameter in Singkil Watershed include: hydrology characteristics of Singkil Watershed consisting of minimum debit of 3.60 mm/day, maximum debit 17.80 mm/day, and ratio of maximum/minimum debit is 4.94. Error indicators of Tank model in Singkil Watershed include Coefficient of Correlation (R), which is 0.6471, Mean Absolute Error (MAE) and Root Square Mean Error (RMSE), which are 2.18 and 2.73, respectively. Several parameters obtained include total inflow (3,189.48 mm/year) and total outflow (3,155.64 mm/year) consisting of surface flow 11.75 mm/year, subsurface flow (669.84 mm/year), intermediate flow (62.05 mm/year), sub-base flow (0.74 mm/year), and base flow (2,411.26 mm/year). Based on the total base flow, the total volume of water availability flowing in Singkil River reaches 12,164 x 106 m3/year. The potential of water resources in Singkil Watershed for agriculture is 3,438.4 x 106 m3/year